(p‐ClPhSe)2 Reduces Hepatotoxicity Induced by Monosodium Glutamate by Improving Mitochondrial Function in Rats. Issue 9 (28th April 2017) - Quines, Caroline B.; Chagas, Pietro M.; Hartmann, Diane; Carvalho, Nélson R.; Soares, Félix A.; Nogueira, Cristina W.
ABSTRACT: It is has been demonstrated that mitochondrial dysfunction, oxidative stress, and chronic inflammatory process are associated with progress of morbid obesity in human patients. For this reason, the searching for safe and effective antiobesity drugs has been the subject of intense research. In this context, the organic selenium compounds have attracted much attention due to their pharmacological properties, such as antihyperglycemic, antioxidant, and anti‐inflammatory. The aim of this study was to evaluate the hepatoprotective action of p ‐chloro‐diphenyl diselenide ( p ‐ClPhSe)2, an organic selenium compound, in a model of obesity induced by monosodium glutamate (MSG) administration in rats. Wistar rats were treated during the first ten postnatal days with MSG (4 g/kg by subcutaneous injections) and received ( p ‐ClPhSe)2 (10 mg/kg, intragastrically) from 90th to 97th postnatal day. Mitochondrial function, purine content and the levels of proteins involved in apoptotic (poly [ADP‐ribose] polymerase [PARP]) and inflammatory processes (inducible nitric oxide synthases [iNOS] and p38) were determined in the liver of rats. The present study, demonstrated that postnatal administration of MSG to male rats induced a mitochondrial dysfunction, accompanied by oxidative stress and an increase in the ADP levels, without altering the efficiency of phosphorylation in the liver of adult rats. Furthermore, the MSG administration also induces hepatotoxicity, through an increase in PARP, iNOS, and p38 levels. ( p ‐ClPhSe)2 treatment had beneficial effects against mitochondrial dysfunction, oxidative stress, and modulated protein markers of apoptosis and inflammation in the liver of MSG‐treated rats. J. Cell. Biochem. 118: 2877–2886, 2017. © 2017 Wiley Periodicals, Inc. Abstract : ( p ‐ClPhSe)2 treatment had beneficial effects against mitochondrial dysfunction ( p ‐ClPhSe)2 treatment demonstrated an antioxidant effect ( p ‐ClPhSe)2 treatment modulated protein markers of apoptosis and inflammation in the liver.